2008
DOI: 10.1098/rspa.2008.0221
|View full text |Cite
|
Sign up to set email alerts
|

A semi-analytical model for oblique impacts of elastoplastic spheres

Abstract: Results of finite-element analysis (FEA) of oblique impacts of elastic and elastic, perfectly plastic spheres with an elastic flat substrate are presented. The FEA results are in excellent agreement with published data available in the literature. A simple model is proposed to predict rebound kinematics of the spheres during oblique impacts. In this model, the oblique impacts are classified into two regimes: (i) persistent sliding impact, in which sliding occurs throughout the impact, the effect of tangential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 39 publications
3
48
0
1
Order By: Relevance
“…Several analytical and semi-empirical models have been developed to evaluate µ and e w in terms of flow parameters such as the impact velocity, impact angle, particle spin and the particle and wall properties [25][26][27][28][29]. While it has been shown that the frictional coefficient significantly affects the collision regime (sliding/non-sliding) [25], fluidization predictions are not sensitive to e w in the range 0.7-1.0 [1,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several analytical and semi-empirical models have been developed to evaluate µ and e w in terms of flow parameters such as the impact velocity, impact angle, particle spin and the particle and wall properties [25][26][27][28][29]. While it has been shown that the frictional coefficient significantly affects the collision regime (sliding/non-sliding) [25], fluidization predictions are not sensitive to e w in the range 0.7-1.0 [1,30].…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to determine φ in situ, Li and Benyahia [1] used the classic rigid-body theory in conjunction with the semi-analytical model for oblique collisions by Wu et al [29] to obtain φ in terms of µ and e w through numerical integration. The derived polynomial expression was further used in a series of 2D simulations for bubbling and circulating fluidized beds and found to be consistent with trends in literature [34].…”
Section: Introductionmentioning
confidence: 99%
“…3a) should be regarded as the reference path, which, in turn, represents the actual path for the spheres of equal elastic moduli. Using formulae (13,14), any path can be reconstructed from the specified overlap and used for calculation of frictional dissipation referred to the contact path.…”
Section: The Main Parameters Of Contact Geometrymentioning
confidence: 99%
“…However, for a non-proportional loading, Elata and Berryman [13] found that the slip regime has to be taken into account, even for identical spheres, and solution becomes path-dependent. The semi-analytical model for oblique impacts of elasto-plastic spheres was proposed and verified by FEM and experiments in [14]. In [15,16], analyzing the relative sphere motion along a specified linear trajectory without the initially activated contact zone, it was demonstrated that both normal and tangential forces vary proportionally, generating the continuing evolution of the sliding regime without the initial slip mode.…”
Section: Introductionmentioning
confidence: 99%
“…In Maw's model, an elastic oblique impact was considered describing the normal forces by Hertz contact theory without any energy loss in this direction, resulting in the coefficient of restitution equal to one. By examination of the FEM-based results from the rebound kinematics of elastic and elastoplastic spheres, a simple semi-analytical model accounting for impact velocity, impact angle and degree of plastic deformation, was proposed by Wu et al [14].…”
Section: Introductionmentioning
confidence: 99%